Direct estimate of the internal π-donation to the carbene centre within N-heterocyclic carbenes and related molecules - Andrada, Diego M.; Holzmann, Nicole; Hamadi, Thomas; Frenking, Gernot (Beilstein Journal of Organic Chemistry, 2015)
Fifteen cyclic and acylic carbenes have been calculated with density functional theory at the BP86/def2-TZVPP level. The strength of the internal X→p(π) π-donation of heteroatoms and carbon which are bonded to the C(II) atom is estimated with the help of NBO calculations and with an energy decomposition analysis. The investigated molecules include N-heterocyclic carbenes (NHCs), the cyclic alkyl(amino)carbene (cAAC), mesoionic carbenes and ylide-stabilized carbenes. The bonding analysis suggests that the carbene centre in cAAC and in diamidocarbene have the weakest X→p(π) π-donation while mesoionic carbenes possess the strongest π-donation.
Keywords: bonding analysis; N-heterocyclic carbenes; π-donation

(untitled) - Arduengo, A. J., III; Harlow, R. L.; Kline, M. (J. Am. Chem. Soc., 1991)

(untitled) - Bourissou, D.; Guerret, O.; Gabbaï, F. P.; Bertrand, G. (Chem. Rev., 2000)

(untitled) - Schuster, O.; Yang, L.; Raubenheimer, H. G.; Albrecht, M. (Chem. Rev., 2009)

(untitled) - Hopkinson, M. N.; Richter, C.; Schedler, M.; Glorius, F. (Nature, 2014)

(untitled) - Benhamou, L.; Chardon, E.; Lavigne, G.; Bellemin-Laponnaz, S.; César, V. (Chem. Rev., 2011)

(untitled) - Martin, D.; Melaimi, M.; Soleilhavoup, M.; Bertrand, G. (Organometallics, 2011)

(untitled) - Melaimi, M.; Soleilhavoup, M.; Bertrand, G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Canac, Y.; Soleilhavoup, M.; Conejero, S.; Bertrand, G. (J. Organomet. Chem., 2004)

(untitled) - Díez-González, S.; Marion, N.; Nolan, S. P. (Chem. Rev., 2009)

(untitled) - Levin, E.; Ivry, E.; Diesendruck, C. E.; Lemcoff, N. G. (Chem. Rev., 2015)

(untitled) - Schaper, L.-A.; Hock, S. J.; Herrmann, W. A.; Kühn, F. E. (Angew. Chem., Int. Ed., 2013)

(untitled) - Izquierdo, J.; Hutson, G. E.; Cohen, D. T.; Scheidt, K. A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Radius, U.; Bickelhaupt, F. M. (Coord. Chem. Rev., 2009)

(untitled) - Fèvre, M.; Pinaud, J.; Gnanou, Y.; Vignolle, J.; Taton, D. (Chem. Soc. Rev., 2013)

(untitled) - Enders, D.; Niemeier, O.; Henseler, A. (Chem. Rev., 2007)

(untitled) - Marion, N.; Díez-González, S.; Nolan, S. P. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hahn, F. E.; Jahnke, M. C. (Angew. Chem., Int. Ed., 2008)

(untitled) - Zhang, D.; Zi, G. (Chem. Soc. Rev., 2015)

(untitled) - Nelson, D. J. (Eur. J. Inorg. Chem., 2015)

(untitled) - Soleilhavoup, M.; Bertrand, G. (Acc. Chem. Res., 2015)

(untitled) - Wang, Y.; Robinson, G. H. (Inorg. Chem., 2014)

(untitled) - Wilson, D. J. D.; Dutton, J. L. (Chem. – Eur. J., 2013)

(untitled) - Wang, Y.; Robinson, G. H. (Dalton Trans., 2012)

(untitled) - Wang, Y.; Robinson, G. H. (Inorg. Chem., 2011)

(untitled) - Rivard, E. (Dalton Trans., 2014)

(untitled) - Martin, C. D.; Soleilhavoup, M.; Bertrand, G. (Chem. Sci., 2013)

(untitled) - Martin, D.; Soleilhavoup, M.; Bertrand, G. (Chem. Sci., 2011)

(untitled) - Power, P. P. (Nature, 2010)

(untitled) - de Frémont, P.; Marion, N.; Nolan, S. P. (Coord. Chem. Rev., 2009)

(untitled) - Regitz, M. (Angew. Chem., Int. Ed. Engl., 1991)

(untitled) - Arduengo, A. J., III; Rasika Dias, H. V.; Harlow, R. L.; Kline, M. (J. Am. Chem. Soc., 1992)

(untitled) - Arduengo, A. J., III (Acc. Chem. Res., 1999)

(untitled) - Herrmann, W. A. (Angew. Chem., Int. Ed., 2002)

(untitled) - Jacobsen, H.; Correa, A.; Poater, A.; Costabile, C.; Cavallo, L. (Coord. Chem. Rev., 2009)

(untitled) - Jacobsen, H.; Correa, A.; Costabile, C.; Cavallo, L. (J. Organomet. Chem., 2006)

(untitled) - Nemcsok, D.; Wichmann, K.; Frenking, G. (Organometallics, 2004)

(untitled) - Tonner, R.; Heydenrych, G.; Frenking, G. (Chem. – Asian J., 2007)

(untitled) - Hahn, F. E.; Zabula, A. V.; Pape, T.; Hepp, A.; Tonner, R.; Haunschild, R.; Frenking, G. (Chem. – Eur. J., 2008)

(untitled) - Scarborough, C. C.; Grady, M. J. W.; Guzei, I. A.; Gandhi, B. A.; Bunel, E. E.; Stahl, S. S. (Angew. Chem., Int. Ed., 2005)

(untitled) - Iglesias, M.; Beetstra, D. J.; Kariuki, B.; Cavell, K. J.; Dervisi, A.; Fallis, I. A. (Eur. J. Inorg. Chem., 2009)

(untitled) - Lu, W. Y.; Cavell, K. J.; Wixey, J. S.; Kariuki, B. (Organometallics, 2011)

(untitled) - Martin, D.; Lassauque, N.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2012)

(untitled) - Martin, D.; Lassauque, N.; Steinmann, F.; Manuel, G.; Bertrand, G. (Chem. – Eur. J., 2013)

(untitled) - Lavallo, V.; Dyker, C. A.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2008)

(untitled) - Fernández, I.; Dyker, C. A.; DeHope, A.; Donnadieu, B.; Frenking, G.; Bertrand, G. (J. Am. Chem. Soc., 2009)

(untitled) - Aldeco-Perez, E.; Rosenthal, A. J.; Donnadieu, B.; Parameswaran, P.; Frenking, G.; Bertrand, G. (Science, 2009)

(untitled) - Guisado-Barrios, G.; Bouffard, J.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2010)

(untitled) - Borthakur, B.; Phukan, A. K. (Chem. – Eur. J., 2015)

(untitled) - Nakafuji, S.-y.; Kobayashi, J.; Kawashima, T. (Angew. Chem., Int. Ed., 2008)

(untitled) - Asay, M.; Donnadieu, B.; Baceiredo, A.; Soleilhavoup, M.; Bertrand, G. (Inorg. Chem., 2008)

(untitled) - Fürstner, A.; Alcarazo, M.; Radkowski, K.; Lehmann, C. W. (Angew. Chem., Int. Ed., 2008)

(untitled) - Hudnall, T. W.; Bielawski, C. W. (J. Am. Chem. Soc., 2009)

(untitled) - Hudnall, T. W.; Tennyson, A. G.; Bielawski, C. W. (Organometallics, 2010)

(untitled) - César, V.; Lugan, N.; Lavigne, G. (Chem. – Eur. J., 2010)

(untitled) - Braun, M.; Frank, W.; Reiss, G. J.; Ganter, C. (Organometallics, 2010)

(untitled) - Lavallo, V.; Canac, Y.; Präsang, C.; Donnadieu, B.; Bertrand, G. (Angew. Chem., Int. Ed., 2005)

(untitled) - Jazzar, R.; Dewhurst, R. D.; Bourg, J.-B.; Donnadieu, B.; Canac, Y.; Bertrand, G. (Angew. Chem., Int. Ed., 2007)

(untitled) - Díez-González, S.; Nolan, S. P. (Coord. Chem. Rev., 2007)

(untitled) - Curran, D. P.; Solovyev, A.; Makhlouf Brahmi, M.; Fensterbank, L.; Malacria, M.; Lacôte, E. (Angew. Chem., Int. Ed., 2011)

(untitled) - Frenking, G.; Tonner, R.; Klein, S.; Takagi, N.; Shimizu, T.; Krapp, A.; Pandey, K. K.; Parameswaran, P. (Chem. Soc. Rev., 2014)

(untitled) - Dröge, T.; Glorius, F. (Angew. Chem., Int. Ed., 2010)

(untitled) - Nelson, D. J.; Nolan, S. P. (Chem. Soc. Rev., 2013)

(untitled) - Fantasia, S.; Petersen, J. L.; Jacobsen, H.; Cavallo, L.; Nolan, S. P. (Organometallics, 2007)

(untitled) - Back, O.; Henry-Ellinger, M.; Martin, C. D.; Martin, D.; Bertrand, G. (Angew. Chem., Int. Ed., 2013)

(untitled) - Liske, A.; Verlinden, K.; Buhl, H.; Schaper, K.; Ganter, C. (Organometallics, 2013)

(untitled) - Vummaleti, S. V. C.; Nelson, D. J.; Poater, A.; Gómez-Suárez, A.; Cordes, D. B.; Slawin, A. M. Z.; Nolan, S. P.; Cavallo, L. (Chem. Sci., 2015)

(untitled) - Alcarazo, M.; Stork, T.; Anoop, A.; Thiel, W.; Fürstner, A. (Angew. Chem., Int. Ed., 2010)

(untitled) - Tukov, A. A.; Normand, A. T.; Nechaev, M. S. (Dalton Trans., 2009)

(untitled) - Bernhammer, J. C.; Frison, G.; Huynh, H. V. (Chem. – Eur. J., 2013)

(untitled) - Huynh, H. V.; Frison, G. (J. Org. Chem., 2013)

(untitled) - Comas-Vives, A.; Harvey, J. N. (Eur. J. Inorg. Chem., 2011)

(untitled) - Rezabal, E.; Frison, G. (J. Comput. Chem., 2015)

(untitled) - Crabtree, R. H. (Coord. Chem. Rev., 2013)

(untitled) - Becke, A. D. (Phys. Rev. A, 1988)

(untitled) - Perdew, J. P. (Phys. Rev. B, 1986)

(untitled) - Weigend, F.; Ahlrichs, R. (Phys. Chem. Chem. Phys., 2005)

(untitled) - Peng, C.; Ayala, P. Y.; Schlegel, H. B.; Frisch, M. J. (J. Comput. Chem., 1996)

(untitled) - McIver, J. W., Jr; Komornicki, A. (J. Am. Chem. Soc., 1972)

Gaussian 09, Revision C.01 (Gaussian, Inc., 2009)

(untitled) - Wiberg, K. B. (Tetrahedron, 1968)

(untitled) - Reed, A. E.; Weinstock, R. B.; Weinhold, F. (J. Chem. Phys., 1985)

(untitled) - Reed, A. E.; Curtiss, L. A.; Weinhold, F. (Chem. Rev., 1988)

GENNBO, 5.9 (Theoretical Chemistry Institute, University of Wisconsin, 2009)

(untitled) - Van Lenthe, E.; Baerends, E. J. (J. Comput. Chem., 2003)

(untitled) - Van Lenthe, E.; Baerends, E. J.; Snijders, J. G. (J. Chem. Phys., 1993)

(untitled) - te Velde, G.; Bickelhaupt, F. M.; Baerends, E. J.; Fonseca Guerra, C.; van Gisbergen, S. J. A.; Snijders, J. G.; Ziegler, T. (J. Comput. Chem., 2001)

(untitled) - Morokuma, K. (J. Chem. Phys., 1971)

(untitled) - Ziegler, T.; Rauk, A. (Inorg. Chem., 1979)

(untitled) - Ziegler, T.; Rauk, A. (Inorg. Chem., 1979)

(untitled) - Bickelhaupt, F. M.; Nibbering, N. M. M.; Van Wezenbeek, E. M.; Baerends, E. J. (J. Phys. Chem., 1992)

(untitled) - Frenking, G.; Wichmann, K.; Fröhlich, N.; Loschen, C.; Lein, M.; Frunzke, J.; Rayón, V. M. (Coord. Chem. Rev., 2003)

(untitled) - Krapp, A.; Bickelhaupt, F. M.; Frenking, G. (Chem. – Eur. J., 2006)

(untitled) - Kovács, A.; Esterhuysen, C.; Frenking, G. (Chem. – Eur. J., 2005)

(untitled) - Mitoraj, M. P.; Michalak, A.; Ziegler, T. (J. Chem. Theory Comput., 2009)

(untitled) - Mitoraj, M.; Michalak, A. (Organometallics, 2007)

(untitled) - Michalak, A.; Mitoraj, M.; Ziegler, T. (J. Phys. Chem. A, 2008)

(untitled) - Mitoraj, M.; Michalak, A. (J. Mol. Model., 2008)

(untitled) - Hahn, F. E.; Wittenbecher, L.; Boese, R.; Bläser, D. (Chem. – Eur. J., 1999)

(untitled) - Arduengo, A. J., III; Goerlich, J. R.; Marshall, W. J. (J. Am. Chem. Soc., 1995)

(untitled) - Alder, R. W.; Allen, P. R.; Murray, M.; Orpen, A. G. (Angew. Chem., Int. Ed. Engl., 1996)

(untitled) - Korotkikh, N. I.; Rayenko, G. F.; Shvaika, O. P.; Pekhtereva, T. M.; Cowley, A. H.; Jones, J. N.; Macdonald, C. L. B. (J. Org. Chem., 2003)

(untitled) - Arduengo, A. J., III; Goerlich, J. R.; Marshall, W. J. (Liebigs Ann./Recl., 1997)

(untitled) - Pyykkö, P.; Atsumi, M. (Chem. – Eur. J., 2009)

(untitled) - Heinemann, C.; Müller, T.; Apeloig, Y.; Schwarz, H. (J. Am. Chem. Soc., 1996)

(untitled) - Tuononen, H. M.; Roesler, R.; Dutton, J. L.; Ragogna, P. J. (Inorg. Chem., 2007)

(untitled) - Boehme, C.; Frenking, G. (J. Am. Chem. Soc., 1996)

(untitled) - Mondal, K. C.; Roesky, H. W.; Schwarzer, M. C.; Frenking, G.; Niepötter, B.; Wolf, H.; Herbst-Irmer, R.; Stalke, D. (Angew. Chem., Int. Ed., 2013)

(untitled) - Mondal, K. C.; Roesky, H. W.; Schwarzer, M. C.; Frenking, G.; Tkach, I.; Wolf, H.; Kratzert, D.; Herbst-Irmer, R.; Niepötter, B.; Stalke, D. (Angew. Chem., Int. Ed., 2013)

(untitled) - Singh, A. P.; Samuel, P. P.; Roesky, H. W.; Schwarzer, M. C.; Frenking, G.; Sidhu, N. S.; Dittrich, B. (J. Am. Chem. Soc., 2013)

(untitled) - Weinberger, D. S.; Melaimi, M.; Moore, C. E.; Rheingold, A. L.; Frenking, G.; Jerabek, P.; Bertrand, G. (Angew. Chem., Int. Ed., 2013)

(untitled) - Samuel, P. P.; Mondal, K. C.; Roesky, H. W.; Hermann, M.; Frenking, G.; Demeshko, S.; Meyer, F.; Stückl, A. C.; Christian, J. H.; Dalal, N. S.; Ungur, L.; Chibotaru, L. F.; et al. (Angew. Chem., Int. Ed., 2013)

(untitled) - Mondal, K. C.; Samuel, P. P.; Roesky, H. W.; Carl, E.; Herbst-Irmer, R.; Stalke, D.; Schwederski, B.; Kaim, W.; Ungur, L.; Chibotaru, L. F.; Hermann, M.; Frenking, G. (J. Am. Chem. Soc., 2014)

(untitled) - Weinberger, D. S.; Amin Sk, N.; Mondal, K. C.; Melaimi, M.; Bertrand, G.; Stückl, A. C.; Roesky, H. W.; Dittrich, B.; Demeshko, S.; Schwederski, B.; Kaim, W.; Jerabek, P.; et al. (J. Am. Chem. Soc., 2014)

(untitled) - Mondal, K. C.; Samuel, P. P.; Roesky, H. W.; Aysin, R. R.; Leites, L. A.; Neudeck, S.; Lübben, J.; Dittrich, B.; Holzmann, N.; Hermann, M.; Frenking, G. (J. Am. Chem. Soc., 2014)

(untitled) - Roy, S.; Mondal, K. C.; Meyer, J.; Niepötter, B.; Köhler, C.; Herbst-Irmer, R.; Stalke, D.; Dittrich, B.; Andrada, D. M.; Frenking, G.; Roesky, H. W. (Chem. – Eur. J., 2015)

(untitled) - Roy, S.; Stollberg, P.; Herbst-Irmer, R.; Stalke, D.; Andrada, D. M.; Frenking, G.; Roesky, H. W. (J. Am. Chem. Soc., 2015)

(untitled) - Esterhuysen, C.; Frenking, G. (Theor. Chem. Acc., 2004)

(untitled) - Frenking, G.; Wichmann, K.; Fröhlich, N.; Grobe, J.; Golla, W.; Le Van, D.; Krebs, B.; Läge, M. (Organometallics, 2002)